The modified biochars influence nutrient and osmotic statuses and hormonal signaling of mint plants under fluoride and cadmium toxicities - Farhangi-Abriz, Salar; Ghassemi-Golezani, Kazem (Frontiers in Plant Science, 2022)
Chemically modified biochars are a new generation of biochars that have a great ability to absorb and stabilize environmental pollutants. In this research, the physiological performance of mint plants (Mentha crispa L.) under fluoride and cadmium toxicities and biochar treatments was evaluated. Four levels of soil toxicities including non-toxic, 600 mg NaF kg-1 soil, 60 mg Cd kg-1 soil, and 600 mg NaF kg-1 soil + 60 mg Cd kg-1 soil were applied. The biochar addition to the soil was 25 g kg-1 (non-biochar, solid biochar, H2O2, KOH, and H3PO4-modified biochars). The results showed that the application of biochar and especially chemically modified biochars reduced fluoride (about 15-37%) and cadmium (30-52%) contents in mint leaves, while increased soil pH and cation exchange capacity (CEC), nitrogen (12-35%), phosphorus (16-59%), potassium (17-52%), calcium (19-47%), magnesium (28-77%), iron (37-114%), zinc (45-226%), photosynthetic pigments of leaves and plant biomass (about 10-25%) under toxic conditions. The biochar-related treatments reduced the osmotic stress and osmolytes content (proline, soluble proteins, and carbohydrates) in plant leaves. Plant leaf water content was increased by solid and modified biochar, up to 8% in toxic conditions. Furthermore, these treatments reduced the production of stress hormones [abscisic acid (27-55%), salicylic acid (31-50%), and jasmonic acid (6-12%)], but increased indole-3-acetic acid (14-31%) in plants under fluoride and cadmium stresses. Chemically modified biochars reduced fluoride and cadmium contents of plant leaves by about 20% and 22%, respectively, compared to solid biochar. This result clearly shows the superiority of modified biochars in protecting plants from soil pollutants.